The involvement of IL-17A in the murine response to sub-lethal inhalational infection with Francisella tularensis. - Gal Markel (Public Library of Science (PLoS), 2010)
Background Francisella tularensis is an intercellular bacterium often causing fatal disease when inhaled. Previous reports have underlined the role of cell-mediated immunity and IFNgamma in the host response to Francisella tularensis infection. Methodology/principal findings Here we provide evidence for the involvement of IL-17A in host defense to inhalational tularemia, using a mouse model of intranasal infection with the Live Vaccine Strain (LVS). We demonstrate the kinetics of IL-17A production in lavage fluids of infected lungs and identify the IL-17A-producing lymphocytes as pulmonary gammadelta and Th17 cells. The peak of IL-17A production appears early during sub-lethal infection, it precedes the peak of immune activation and the nadir of the disease, and then subsides subsequently. Exogenous airway administration of IL-17A or of IL-23 had a limited yet consistent effect of delaying the onset of death from a lethal dose of LVS, implying that IL-17A may be involved in restraining the infection. The protective role for IL-17A was directly demonstrated by in vivo neutralization of IL-17A. Administration of anti IL-17A antibodies concomitantly to a sub-lethal airway infection with 0.1xLD(50) resulted in a fatal disease. Conclusion In summary, these data characterize the involvement and underline the protective key role of the IL-17A axis in the lungs from inhalational tularemia.